Sandwich‐like Catalyst–Carbon–Catalyst Trilayer Structure as a Compact 2D Host for Highly Stable Lithium–Sulfur Batteries. (18th May 2020) - Li, Rongrong; Peng, Hongjie; Wu, Qingping; Zhou, Xuejun; He, Jiang; Shen, Hangjia; Yang, Minghui; Li, Chilin
Abstract: Herein, we propose the construction of a sandwich‐structured host filled with continuous 2D catalysis–conduction interfaces. This MoN‐C‐MoN trilayer architecture causes the strong conformal adsorption of S/Li2 S x and its high‐efficiency conversion on the two‐sided nitride polar surfaces, which are supplied with high‐flux electron transfer from the buried carbon interlayer. The 3D self‐assembly of these 2D sandwich structures further reinforces the interconnection of conductive and catalytic networks. The maximized exposure of adsorptive/catalytic planes endows the MoN‐C@S electrode with excellent cycling stability and high rate performance even under high S loading and low host surface area. The high conductivity of this trilayer texture does not compromise the capacity retention after the S content is increased. Such a job‐synergistic mode between catalytic and conductive functions guarantees the homogeneous deposition of S/Li2 S x, and avoids thick and devitalized accumulation (electrode passivation) even after high‐rate and long‐term cycling. Abstract : New approach to lithium–sulfur batteries : A trilayer MoN‐C‐MoN sandwich structure characterized by a continuous 2D catalysis–conduction contact interface was prepared as a sulfur cathode host. The two MoN outer layers adsorb LiPSs/Li2 S2 /Li2 S products and accelerate their conversion, while the C interlayer acts as a high‐flux electron transfer pathway to reinforce the overall conductivity of the sandwich structure. In this way the accumulation of dead Li2 S2 /Li2 S can be avoided even after extended cycling.